Oligarchy - Winters, Jeffrey A. (Jeffrey Alan), 1960-; ProQuest (Firm) (Cambridge [England] ; New York : Cambridge University Press, 2011)
"The common thread for oligarchs across history is that wealth defines them, empowers them, and inherently exposes them to threats. The existential motive of all oligarchs is wealth defense. These variations yield four types of oligarchy: warring, ruling, sultanistic, and civil"--
"For centuries, oligarchs were viewed as empowered by wealth, an idea muddled by elite theory early in the twentieth century. The common thread for oligarchs across history is that wealth defines them, empowers them, and inherently exposes them to threats. The existential motive of all oligarchs is wealth defense. How they respond varies with the threats they confront, including how directly involved they are in supplying the coercion underlying all property claims, and whether they act separately or collectively. These variations yield four types of oligarchy: warring, ruling, sultanistic, and civil. Oligarchy is not displaced by democracy but rather is fused with it. Moreover, the rule of law problem in many societies is a matter of taming oligarchs. Cases studied in this book include the United States, ancient Athens and Rome, Indonesia, the Philippines, Singapore, medieval Venice and Siena, mafia commissions in the United States and Italy, feuding Appalachian families, and early chiefs cum oligarchs dating from 2300 BCE"--
Machine generated contents note: 1. Preface; 2. Material foundations of oligarchy; 3. Warring oligarchies; 4. Ruling oligarchies; 5. Sultanistic oligarchies; 6. Civil oligarchies; 7. Conclusions.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Oligarchy; Electronic books